THE YOUTH SELFGOVERNMENT IN THE DEVELOPMENT OF SCIENCE AS A BASIS FOR PERSONNEL POTENTIAL FORMATION - Denis Y. Zakharov; Lubov’ A. Kravtsova; Yana V. Shcherbatyuk (Высшее образование в России)
Abstract. In the «fight for minds» of the Russian youth the modern education system should rely on active and initiative representatives of a new generation of researches. For this purpose creation of the effective tool by means of which they can interact with themselves, administration of university, authorities and future employers is necessary. The recipe of such tool originates in the Soviet era N the youth self-government organizations. Adaptation of this tool to modern, rapidly changing conditions is the most important task of educational and scientific community.